Chemical Composition and Antimicrobial Activity of Essential Oils of Stems of Macleaya cordata (Willd) R. Br. - Li, Chunmei; Yu, Jianping (Asian Journal of Chemistry, 2014)
The essential oil from the stems of Macleaya cordata R.Br. obtained by hydrodistillation was analyzed by gas chromatography/mass spectrometry. Fifty compounds consisting up to 99.17 % of the essential oil were identified by GC and GC/MS analysis. The essential oil exhibited potential antimicrobial activity against all tested microorganisms, with diameters of inhibition zones ranging from 7.7 ± 0.6 to 16.9 ± 0.8 mm and MIC values from 125 to 500 μg/mL. To understand the antibacterial mechanism of the essential oil, we selected the sensitive bacterium R. solanacarum as model to observe of the action of essential oils of M. cordata on the membrane structure by SEM. The treated cell membranes were damaged severely; resulting in cell atrophy and condenses into clusters, lost the original rod structure. The results presented here indicate that the essential oil of M. cordata has antimicrobial properties and is therefore a potential source of antimicrobial agents for many industries in the future.